2021
DOI: 10.48550/arxiv.2103.04380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Full Body Avatar-Based Telepresence System for Dissimilar Spaces

Leonard Yoon,
Dongseok Yang,
Choongho Chung
et al.

Abstract: Figure 1: Our telepresence system allows for different room environments by retargeting the user's placement and deictic gesture to the remote avatar so as to preserve the user's context of placement and interaction. In this figure, a user in the left space is sitting facing a display and pointing at a point in the display. The user is represented in the right space by a male avatar sitting on the right side of a display, pointing at the corresponding point in the display. A user sitting in front of the displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To cope with room disparities, researchers have developed prototype systems that demonstrate various approaches to aligning distributed spaces. Solutions involve discretizing environments into functional spaces [45], warping the avatar's deictic gestures based on landmarks [44], adapting avatar movements [5,14,43]), and computing an optimal partial alignment [21]. We revisit these solutions in more detail in section 3.…”
Section: From Blended Interaction Spaces To Blended Realitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with room disparities, researchers have developed prototype systems that demonstrate various approaches to aligning distributed spaces. Solutions involve discretizing environments into functional spaces [45], warping the avatar's deictic gestures based on landmarks [44], adapting avatar movements [5,14,43]), and computing an optimal partial alignment [21]. We revisit these solutions in more detail in section 3.…”
Section: From Blended Interaction Spaces To Blended Realitiesmentioning
confidence: 99%
“…Studies have shown that passive haptics supports a better sense of presence in the virtual environment [13,37], which can be used in systems for aligning physical and virtual environments [11,37,41]. Moreover, providing landmarks in the physical environment can enhance the ability to spatially reference shared objects [25,44].…”
Section: Physicality and Collaboration Around Information Surfacesmentioning
confidence: 99%
“…To retarget a user's deictic gestures to an avatar, gesture retargeting approaches have been proposed [KL20,YYCL21]. The user's head direction and arm posture are adjusted to make the avatar point to the same position toward the remote object as that toward the corresponding local object.…”
Section: Telepresence Using a Full-body Avatarmentioning
confidence: 99%
“…For example, several approaches deal with the modification of the user root path during locomotion without supporting the user's interaction with objects [CWS18,TSDS19] or only support human-object interaction motions within a pre-defined area around an object [KPBL16]. Other approaches propose placement retargeting methods for an avatar [YYK * 20] with upper-body gestures only [KL20,YYCL21]. Despite their reported successes, these approaches are not effective in providing co-presence to par-ticipants in a telepresence system due to the lack of general handling of continuous full-body motions including both locomotion and object interaction motions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation